A Novel Tau Antibody Detecting the First Amino-Terminal Insert Reveals Conformational Differences Among Tau Isoforms - Verelst, Joke; Geukens, Nick; Eddarkaoui, Sabiha; Vliegen, Dorien; De Smidt, Elien; Rosseels, Joëlle; Franssens, Vanessa; Molenberghs, Sofie; Francois, Cindy; Stoops, Erik; Bjerke, Maria; Engelborghs, Sebastiaan; et al. (Frontiers in Molecular Biosciences, 2020)
As human Tau undergoes pathologically relevant post-translational modifications when expressed in yeast, the use of humanized yeast models for the generation of novel Tau monoclonal antibodies has previously been proven to be successful. In this study, human Tau2N4R-ΔK280 purified from yeast was used for the immunization of mice and subsequent selection of high affinity Tau-specific monoclonal antibodies. The characterization of four novel antibodies in different Tau model systems yielded a phosphorylation-dependent antibody (15A10), an antibody directed to the first microtubule-binding repeat domain (16B12), a carboxy-terminal antibody (20G10) and an antibody targeting an epitope on the hinge of the first and second amino-terminal insert (18F12). The latter was found to be conformation-dependent, suggesting structural differences between the Tau splicing isoforms and allowing insight in the roles played by the amino-terminal inserts. As this monoclonal antibody also has the capacity to detect tangle-like structures in different transgenic Tau mice and neurofibrillary tangles in brain sections of patients diagnosed with Alzheimer’s disease, we also tested the diagnostic potential of 18F12 in a pilot study and found this monoclonal antibody to have the ability to discriminate Alzheimer’s disease patients from control individuals based on increased Tau levels in the cerebrospinal fluid.